Socio-Economic and Demographic Determinants of Pulmonary Tuberculosis among Adults in Indonesia - Nurafni Nurafni; Ema Novita Deniati; Siti Nurrochman; Supriyadi Supriyadi (FORIKES, 2026)
Tuberculosis remains a major public health challenge in Indonesia, with a substantial disease burden particularly affecting the productive-age population. Beyond biological susceptibility, socio-economic disparities are recognized as key contributors to the risk of pulmonary tuberculosis. However, comprehensive analyses using nationally representative data remain limited. This study aimed to examine the association between socio-economic determinants and the incidence of pulmonary tuberculosis among adults in Indonesia. An observational analytic study with a cross-sectional design was conducted using combined secondary data from the 2023 Indonesian Health Survey and the National Socio-Economic Survey, comprising a total of 174,062 respondents. Socio-economic variables included educational level, income, housing density, housing environmental quality, and access to health services, while age, sex, place of residence, and occupation were treated as confounding variables. Data analysis consisted of univariate procedures, bivariate tests using Chi-square and Mann–Whitney, and multivariate analysis using multiple logistic regression. The findings indicated that low educational level (p<0.001; OR=1.8), low income (p=0.042; OR=0.8), high housing density (p=0.009; OR=1.4), male sex (p<0.001; OR=1.8), urban residence (p=0.029; OR=1.4), age (p<0.001; OR=1.02), and occupation (p=0.009) were significantly associated with pulmonary TB incidence. In conclusion, these results demonstrate that socio-economic and demographic factors play a substantial role in the occurrence of pulmonary tuberculosis in Indonesia. Strengthening TB control efforts through socio-economic improvement, enhanced educational attainment, and targeted promotive and preventive interventions for high-risk groups is essential to reduce disease transmission.Keywords: tuberculosis; socio-economic factors; adult